INCREASING STUDENTS’ WIRITING ABILITY THROUGH INTERACTIVE WRITING MODEL AT SMAN 1 ENREKANG - Intan Hardiyanti Hasri; Andi Tenri Ampa; Ilmiah (Journal of Language Testing and Assessment, 2021)
This research aimed to know the increasing students’ writing ability in descripitive and recount text through Interactive Writing Model at the first grade SMAN 1 ENREKANG. The method of this research was pre-experimental research. The sample of this research. The sample of this research consisted of experiment class. Namely class X IPA 5 was 30 students. In the class used Interactive Writing Model. The sample was taken by Random Sampling Technique. Based on the findings, it was found that the value of t-test in writing is descriptive text is greater than the ratio on t-table (3.770) > (2.756) and in recount text t-test is greater than ratio on t-table also (5.420) > (2.756). Based on the table it can be conclude that the alternative hypothesis is accepted. It means that there was increased in the students’ writing descriptive and recount text before and after gave treatment used interactive writing model. Therefore, that result of the pre-test and post-test was significance different. Based on the descriptive, the pre-test and post-test prove the post-test is higher. Based on the explanation, Interactive Writing Model can increase the students’ writing ability in descriptive and recount text.